A Study of Leadership Style, Organizational Culture, Employee Skills, and Incentives In The Context of Employee Productivity at Padi Aqiqah Purwokerto - Cakti Indra Gunawan; Hendrik Suhendri (International Journal of Management and Business, 2025)
In today's era of globalization and information, the role of human resources is crucial for companies facing high competition in the free market. Organizations should have a human resources policy. This is because human resource planning is closely linked to solving problems that frequently arise within groups and organizations. The purpose of this study is to examine leadership style, organizational culture, employee skills, and incentives in the context of on employee productivity at Padi Aqiqah Purwokerto. The research method uses descriptive analysis. The results of the study indicate that not all elements in employee productivity are supported by leadership style, organizational culture, employee skills, and incentives. An interesting finding shows that worker skills do not necessarily support employee work productivity.